Self-Control and Digital Well-Being Among University Students: A Mediation Analysis of Online Mindfulness within a Self-Regulation Framework - Muslikah, M; Yuliati Hotifah; Mulawarman, M; Kunwijaya, Indrajati; Mahfud, Ashari; Hariyadi, Sigit; Dwy, Susantika; Latihifah, Alvia Ainil (Universitas Negeri Padang, 2025)
Recent frameworks in digital flourishing and self-regulation highlight that intrapersonal regulatory abilities are vital in shaping individuals’ well-being in online environments; however, empirical evidence linking these mechanisms among university students remains scarce. To address this gap, this study investigates the relationship between self-control and digital well-being and examines online mindfulness as a mediating psychological factor. A total of 300 undergraduate students (122 males and 178 females; aged 18–23 years) completed validated measures of self-control, online mindfulness (adapted from MAAS), and digital well-being. A mediation analysis using Hayes’ PROCESS macro with 5,000 bootstrap samples was conducted. Self-control significantly predicted digital well-being directly (β = .348, SE = 0.053, t = 6.61, p < .001; 95% CI [.244, .452]) and indirectly through online mindfulness (β = .178; 95% CI [.118, .246]), indicating partial mediation. Self-control also strongly predicted online mindfulness (β = .421, SE = .053, t = 7.89, p < .001), and online mindfulness significantly predicted digital well-being after controlling for self-control (β = .422, SE = .043, t = 9.81, p < .001). Gender-specific analyses showed consistent mediation patterns for males (indirect effect = 0.167; 95% CI [.094, .248]) and females (indirect effect = .184; 95% CI [.122, .259]). These findings enhance theoretical understanding by clarifying how self-regulatory capacity boosts digital well-being through mindful online awareness. Practically, the results provide an empirical foundation for designing digital-based guidance and counselling interventions that encourage online mindfulness to promote healthier technology engagement among students.